2016
DOI: 10.1111/jne.12335
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol Exposure Early in Life Programs Daily and Circadian Activity Rhythms in Adult Mice

Abstract: Hormone signalling during critical periods organises the adult circadian timekeeping system by altering adult hormone sensitivity and shaping fundamental properties of circadian rhythmicity. However, the timing of when developmental oestrogens modify the timekeeping system is poorly understood. To test the hypothesis that alterations in postnatal oestrogenic signalling organise adult daily activity rhythms, we utilised aromatase knockout mice (ArKO), which lack the enzyme required for oestradiol synthesis. ArK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Although sex differences in phase-resetting were not analyzed per se , it is clear when comparing saline-treated groups that the magnitude of phase-delay was similar between males and females (~1.5 h). This is consistent with another recent study showing no difference in photic phase-shifting between wildtype male and female mice at ZT14 (Royston et al, 2016). However, these and other authors (Blattner and Mahoney, 2013) also report evidence that estrogen modulates phase-resetting and other circadian measures (discussed above).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although sex differences in phase-resetting were not analyzed per se , it is clear when comparing saline-treated groups that the magnitude of phase-delay was similar between males and females (~1.5 h). This is consistent with another recent study showing no difference in photic phase-shifting between wildtype male and female mice at ZT14 (Royston et al, 2016). However, these and other authors (Blattner and Mahoney, 2013) also report evidence that estrogen modulates phase-resetting and other circadian measures (discussed above).…”
Section: Discussionsupporting
confidence: 94%
“…Stowie and Glass (2015) also noted longer alpha and greater bout duration and intensity in adolescent and young adult female C57BL6J mice compared to age-matched males (Stowie and Glass, 2015). Similarly, Royston et al (2016) observed more wheel-running activity in adult female, compared to adult male mice of the same strain, a difference which was enhanced by aromatase deletion and dampened by estradiol (Royston et al, 2016). Longer activity duration has also been observed during DD in young adult (2-3 month old) female Per2 Luc mice on a C57BL6J background (Kuljis et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…An additional experiment with GDX male and female ArKO mice and their respective GDX WT littermates found that exposure to estradiol at postnatal day (PD) 1–5 is essential for programming of circadian locomotor rhythms (Royston, Bunick, & Mahoney, ). Here, they found that OVX females treated with the oil control, irrespective of genotype, were significantly more active than GDX males treated with the oil control.…”
Section: Organizational Regulation Of Circadian Rhythms Through Estromentioning
confidence: 99%
“…Normally, exposure to light in the early subjective night (ZT16, 4 hr after lights‐off) results in a phase delay of activity onset on subsequent days, while exposure to light in the late dark phase (ZT22, 2 hr before lights‐on) results in a phase advance. Early life exposure to estradiol during PD1‐5 appears to organize how the SCN responds to light in the early night in females, but not males (Royston et al., ). Interestingly, OVX WT females treated with early postnatal estradiol had a more robust response to light pulses at ZT16 compared to OVX WT females treated with oil, while OVX ArKO females treated with postnatal estradiol exhibited a phase response similar to OVX WT females.…”
Section: Organizational Regulation Of Circadian Rhythms Through Estromentioning
confidence: 99%
“…In mammals, it is well-established that sex steroid hormones have various organizational effects regulating the development of the circadian neural network and the expression of estrogen and androgen receptors which underlie sexual dimorphism in circadian activity (Hagenauer et al, 2011a(Hagenauer et al, , 2011bHummer et al, 2012;Melo et al, 2010;Royston et al, 2016;Sellix et al, 2013; for a recent review see Hatcher et al, 2020). Our findings that a single acute manipulation of JH levels shortly after adult eclosion from the pupa, resulted in relatively long term effects on the power of circadian rhythms best fit with the forth hypothesis stating that the influence of JH on circadian rhythms is mostly organizational.…”
Section: Discussionmentioning
confidence: 99%